ASEAN-China relations realities and prospects - Saw, Swee-Hock 1931-; Sheng, Lijun; Chin, Kin Wah (Gale virtual reference library, 2005)
"Examines the areas of convergence and divergence in ASEAN-China relations (political, social, and economic) and their possible outcomes."--GVRL description.